Supplement Continuous and Quasi-Supplement Continuous Modules - Ali, Sarah Hassan; Nayef, Mahdi Saleh (Iraqi Journal of Science, 2024)
In this research, we introduce the concepts of -module where (i=1,2,3), as proper generalizations of -conditions, where (i=1,2,3). The relationships between these concepts and previous ones were explained, and a comprehensive description of each was provided. Additionally, by relying on -module, new concepts were developed, such as supplement continuous and quasi-supplement continuous, which represent generalizations of continuous and quasi-continuous. Illustrative examples were provided, and the possibility of their inheritance was discussed.